Beta Function and Gama Function
Beta Function and Gama Function
Beta Function and Gama Function
)
9836395857/ 6290679526
Example:-
1
(𝑖 ) ∫ 𝑥 3 (1 − 𝑥 )4 𝑑𝑥 = 𝛽(4,5)
0
1
(𝑖𝑖 ) ∫0 𝑥 4 (1 − 𝑥 )−2 𝑑𝑥 = 𝛽(5, −1) → not defined, since 𝑚 > 0, 𝑛 > 0
Note:-
i. Beta function is also known as Euler (or, Eulerian) integral of 1st kind and was given its name by
Jacques Binet (inventor of Beta Function) and this function was first studied by Euler and
Legendre.
ii. Application of Beta & Gamma Function:- It has applications in various area e.g. Multiple integrals,
definite integrals, asymptote series, hypergeometric series, number theory, string theory, in
probability (Beta & Gamma distribution) etc.
𝝅/𝟐
(Q.3) Prove that 𝜷(𝒎, 𝒏) = 𝟐 ∫𝟎 𝒔𝒊𝒏𝟐𝒎−𝟏 𝜽 𝒄𝒐𝒔𝟐𝒏−𝟏 𝜽 𝒅𝜽, 𝒎 > 𝟎, 𝒏 > 𝟎
𝝅/𝟐 𝟏 𝒑+𝟏 𝒒+𝟏
Hence 𝑷. 𝑻 ∫𝟎 𝒔𝒊𝒏𝒑 𝜽𝒄𝒐𝒔𝒒 𝜽 𝒅𝜽 = 𝟐 𝜷 ( , ) , 𝒑 > −𝟏, 𝒒 > −𝟏
𝟐 𝟐
1
Solution :-We have 𝛽 (𝑚, 𝑛) = ∫0 𝑥 𝑚−1 (1 − 𝑥 )𝑛−1 𝑑𝑥, 𝑤ℎ𝑒𝑟𝑒 𝑚 > 0, 𝑛 > 0
Let 𝑥 = sin2 𝜃, then 𝑑𝑥 = 2 sin 𝜃 cos 𝜃 𝑑𝜃
𝜋
2
∴ 𝛽(𝑚, 𝑛) = ∫ (𝑠𝑖𝑛2 𝜃 )𝑚−1 (1 − 𝑠𝑖𝑛2 𝜃 )𝑛−1 . 2 sin 𝜃 cos 𝜃 𝑑𝜃
0
𝜋/2
∴ 𝛽(𝑚, 𝑛) = 2 ∫ 𝑠𝑖𝑛2𝑚−1 𝜃 𝑐𝑜𝑠 2𝑛−1 𝜃 𝑑𝜃 , 𝑚 > 0, 𝑛 > 0 … … … (𝑖 ) [𝐅𝐨𝐫𝐦𝐮𝐥𝐚 − 𝟐]
0
2nd part :-
𝑙𝑒𝑡 2𝑚 − 1 = 𝑝 𝑎𝑛𝑑 2𝑛 − 1 = 𝑞
~1~
𝑝+1 𝑞+1
⇒𝑚= ⇒𝑛=
2 2
∴From (𝑖 ), we get
𝜋/2
𝑝+1 𝑞+1
𝛽 ( , ) = 2 ∫ 𝑠𝑖𝑛𝑝 𝜃 𝑐𝑜𝑠 𝑞 𝜃 𝑑𝜃, 𝑤ℎ𝑒𝑟𝑒 𝑚 > 0, 𝑛 > 0 𝑖. 𝑒. 𝑝 > −1, 𝑞 > −1
2 2 0
𝜋/2
1 𝑝+1 𝑞+1
∴ ∫ 𝑠𝑖𝑛𝑝 𝜃 𝑐𝑜𝑠 𝑞 𝜃 𝑑𝜃 = 𝛽 ( , ) where the restrictions are 𝑝 > −1, 𝑞 > −1[𝐅𝐨𝐫𝐦𝐮𝐥𝐚 − 𝟑]
0 2 2 2
𝟏 𝟏
(Q.4) Prove that 𝜷 (𝟐 , 𝟐) = 𝝅
𝜋
1 𝑝+1 𝑞+1
Solution :-We have ∫02 𝑠𝑖𝑛𝑝 𝜃 𝑐𝑜𝑠 𝑞 𝜃 𝑑𝜃 = 2 𝛽 ( , ) , 𝑤ℎ𝑒𝑟𝑒 𝑝 > −1, 𝑞 > −1 → (1)
2 2
Puting 𝑝 = 𝑞 = 0 in (𝑖 ), we have
𝜋
2 1 1 1
∫ 𝑑𝜃 = 𝛽( , )
0 2 2 2
1 1
⇒ 𝛽 ( , ) = 𝜋 [𝐅𝐨𝐫𝐦𝐮𝐥𝐚 − 𝟒]
2 2
∞𝒚𝒎−𝟏 ∞ 𝒚𝒏−𝟏
(Q.5) P.T. 𝜷(𝒎, 𝒏) = ∫𝟎 (𝟏+𝒚)𝒎+𝒏
𝒅𝒚 = ∫𝟎 (𝟏+𝒚)𝒎+𝒏
𝒅𝒚 [CH – 2004]
1
Solution :-We have 𝛽(𝑚, 𝑛) = ∫0 𝑥 𝑚−1 (1 − 𝑥 )𝑛−1 𝑑𝑥, 𝑚 > 0, 𝑛 > 0 … … … … . . (𝑖)
𝑦
Let 𝑥 = 1+𝑦
(1 + 𝑦). 1 − 𝑦. 1 1
⇒ 𝑑𝑥 = 2
𝑑𝑦 = 𝑑𝑦
(1 + 𝑦) (1 + 𝑦 )2
& 𝑥 (1 + 𝑦 ) = 𝑦
⇒ 𝑥 + 𝑥𝑦 = 𝑦
⇒ 𝑦 (1 − 𝑥 ) = 𝑥
𝑥
⇒𝑦=
1−𝑥 ∞
𝑦 𝑚−1 𝑦 𝑛−1 1
∴ 𝛽(𝑚, 𝑛) = ∫ ( ) (1 − ) . 𝑑𝑦
1+𝑦 1+𝑦 (1 + 𝑦)2
0
∞
𝑦 𝑚−1 1 𝑑𝑦
=∫ 𝑚−1
. 𝑛−1
.
(1 + 𝑦 ) (1 + 𝑦 ) (1 + 𝑦 ) 2
0
∞
𝑦 𝑚−1
=∫ 𝑑𝑦 [𝑝𝑟𝑜𝑣𝑒𝑑 ]
(1 + 𝑦)𝑚+𝑛
0
2nd part :-
1 −1
Putting 𝑥 = 1+𝑦 ⇒ 𝑑𝑥 = (1+𝑦)2 𝑑𝑦
𝑎𝑛𝑑 𝑥 + 𝑥𝑦 = 1
1−𝑥
⇒𝑦=
𝑥
From (i), we get
0
1 𝑚−1 1 𝑛−1 𝑑𝑦
𝛽 (𝑚, 𝑛) = − ∫ ( ) (1 − ) .
1+𝑦 1+𝑦 (1 + 𝑦 )2
∞
∞
1 𝑦 𝑛−1 𝑑𝑦
=∫ . .
(1 + 𝑦)𝑚−1 (1 + 𝑦)𝑛−1 (1 + 𝑦)2
0
~2~
∞
𝑦 𝑛−1
= ∫ 𝑑𝑦 [𝑝𝑟𝑜𝑣𝑒𝑑 ]
(1 + 𝑦)𝑚+𝑛
0
Gamma function
Introduction:-
i. The Gamma function was first introduced by the Swiss Mathematician Leonhard Euler (1707-
1783) in his goal to generalise the factorial to non integer values.
ii. Later, because of its great importance, it was studied by other eminent mathematician.
iii. The Gamma function belongs to the category of the special transcendal functions due to the
involvement of the exponential term in its definition.
iv. Gamma function is also called the Eulerian integral of 2nd kind.
∫ 𝑒 −𝑦 . 𝑦 3 𝑑𝑦 = Γ(4)
0
∞
Note:-
i. [NFE] First definition of Gamma function (By Euler in 1730):-
1
Γ(𝑛) = ∫ (− log 𝑡)𝑛−1 𝑑𝑡 , 𝑤ℎ𝑒𝑟𝑒 𝑛 > 0
0
Let − log 𝑡 = 𝑥 ⇒ 𝑡 = 𝑒 −𝑥 ⇒ 𝑑𝑡 = −𝑒 −𝑥 𝑑𝑥
∞
∴ Γ(𝑛) = ∫ 𝑒 −𝑥 𝑥 𝑛−1 𝑑𝑥 , 𝑤ℎ𝑒𝑟𝑒 𝑛 > 0
0
This is the generalised definition.
ii. [NFE] There is a unique function 𝑓: (0, ∞) → (0, ∞) such as log(𝑓(𝑥 )) is convex and 𝑓(1) =
1, 𝑓(𝑥 + 1) = 𝑥𝑓(𝑥 ).
It is also possible to extend this function to negative values by inverting the functional equation
(which becomes a definition identity) for −1 < 𝑥 < 0 as
Γ(𝑥 + 1)
Γ(𝑥 ) =
𝑥
1 1
and for example Γ (− 2) = −2Γ (2). Realisation of this identity allows to define the gamma
function on the whole real axis except on the negative integers (0, −1, −2, … ).
iii. [NFE] Plot of Gamma Function.
~4~
𝐵
𝑙𝑖𝑚
= ∫ 𝑒 −𝑥 𝑑𝑥
𝐵→∞
0
𝑙𝑖𝑚 [ −𝑥 ]𝐵
= −𝑒 0
𝐵→∞
𝑙𝑖𝑚 1 1
= (1 − 𝑒𝐵 ) = 1 [∵ lim 𝑒𝐵 = 0]
𝐵→∞ 𝐵→∞
∴ 𝚪( 𝟏 ) = 𝟏 [𝐅𝐨𝐫𝐦𝐮𝐥𝐚 − 𝟔]
( )
𝒏𝜞 𝒏 , 𝒏 𝐛𝐞 𝐚 + 𝐯𝐞 𝐫𝐞𝐚𝐥 𝐧𝐮𝐦𝐛𝐞𝐫
(Q.3) P.T 𝚪(𝒏 + 𝟏) = { 𝒏! , 𝒊𝒇 𝒏 𝐛𝐞 𝐚 𝐧𝐚𝐭𝐮𝐫𝐚𝐥 𝐧𝐮𝐦𝐛𝐞𝐫 [𝐅𝐨𝐫𝐦𝐮𝐥𝐚 − 𝟕]
𝟎. [𝐅𝐨𝐫𝐦𝐮𝐥𝐚 − 𝟖]
Proof:- Copy from integral calculus of Maity Ghosh.
𝟏
(Q.4) Prove that 𝚪 (𝟐) = √𝝅. [𝐅𝐨𝐫𝐦𝐮𝐥𝐚 − 𝟗]
Γ(𝑚)Γ(𝑛)
Solution :- We have 𝛽 (𝑚, 𝑛) = ,𝑚 > 0, 𝑛 > 0
Γ(𝑚+𝑛)
1
Putting 𝑚 = 𝑛 = 2
~5~
1 1
1 1 Γ (2) Γ (2)
𝛽( , ) =
2 2 1 1
Γ (2 + 2)
1 2
{Γ ( )} 1 1
2
⇒𝜋= [∵ 𝛽 ( , ) = 𝜋] → (𝑝𝑟𝑜𝑣𝑒 𝑖𝑡)
Γ(1) 2 2
1
⇒ Γ ( ) = √π [∵ Γ(1) = 1]
2
Note:-
3 1 1 1 √π 1
Γ ( ) = Γ ( + 1) = . Γ ( ) = [∵ Γ ( ) = √π]
2 2 2 2 2 2
5 3 3 3 3 1 1 3
Γ ( ) = Γ ( + 1) = Γ ( ) = . Γ ( ) = √𝜋
2 2 2 2 2 2 2 4
7 5 3 1 1
Γ( ) = . . .Γ( )
2 2 2 2 2
9 7 5 3 1 1
Γ( ) = . . . .Γ( )
2 2 2 2 2 2
11 9 7 5 3 1 1
Γ( ) = . . . . .Γ( )
2 2 2 2 2 2 2
Γ(6) = 5!
15 11 11 7 3 3
Γ ( ) = Γ ( + 1) = . . Γ( )
4 4 4 4 4 4
∞ 𝟐 √𝝅 ∞ 𝟐
(Q.5) Prove that ∫𝟎 𝒆−𝒙 𝒅𝒙 = . Hence 𝑷. 𝑻 ∫−∞ 𝒆−𝒙 𝒅𝒙 = √𝝅
𝟐
Solution :-
Let 𝑥 2 = 𝑧
⇒ 2𝑥𝑑𝑥 = 𝑑𝑧
𝑑𝑧
⇒ 𝑑𝑥 =
2√𝑧
∞ ∞ ∞
−𝑥 2
𝑑𝑧
1 1
∴ ∫𝑒 𝑑𝑥 = ∫ 𝑒 −𝑧 . = ∫ 𝑒 −𝑧 . 𝑧 −2 𝑑𝑧
2√𝑧 2
0 0 0
1 1 √𝜋 1
= Γ ( )= [∵ Γ ( ) = √𝜋]
2 2 2 2
2nd part :-
∞ 𝐵
−𝑥 2 𝑙𝑖𝑚 2
We have ∫ 𝑒 𝑑𝑥 = ∫ 𝑒 −𝑥 𝑑𝑥
𝐵→∞
−∞ −𝐵
𝐵 𝑎 𝑎
𝑙𝑖𝑚 2
= 2 ∫ 𝑒 −𝑥 𝑑𝑥 [∵ ∫ 𝑓 (𝑥 )𝑑𝑥 = 2 ∫ 𝑓 (𝑥 ) 𝑑𝑥, 𝑖𝑓 𝑓 (−𝑥 ) = 𝑓 (𝑥 )]
𝐵→∞
0 −𝑎 0
∞
2 √𝜋
= 2 ∫ 𝑒 −𝑥 𝑑𝑥 = 2. = √𝜋
2
0
▪
An important result:-
Γ(m)Γ(1 − m) = π cosec mπ, 0 < 𝑚 < 1 [𝐅𝐨𝐫𝐦𝐮𝐥𝐚 − 𝟏𝟎]
Proof: Out of syllabus.
1 3 π 1
(𝑖 )Γ ( ) Γ ( ) = πcosec = √2π [taking m = ]
4 4 4 4
~6~
1 1 π
(𝑖𝑖 )Γ ( ) Γ ( ) = πcosec = π
2 2 2
2
1 1
⇒ {Γ ( )} = 𝜋 ⇒ Γ ( ) = √π
2 2
~7~
∞ 3 ∞ 1/6 𝑑𝑧 1 ∞ 1 1 √𝜋
∴ ∫0 √𝑥 𝑒 −𝑥 𝑑𝑥 = ∫0 𝑧 𝑒 −𝑧 . 3𝑧 2/3 = ∫0 𝑒 −𝑧 . 𝑧 −1/2 𝑑𝑧 = Γ (2) =
3 3 3
∞ 𝟐 𝟏
6. (vi) Prove that ∫𝟎 𝟓−𝒙 𝒅𝒙 = 𝟐 √𝝅.
√𝒍𝒐𝒈 𝟓
∞ 2 ∞ −𝑥2 ∞ 2 log 5
Solution:-We have ∫0 5−𝑥 𝑑𝑥 = ∫0 𝑒 log 5 𝑑𝑥 = ∫0 𝑒 −𝑥 𝑑𝑥 → (𝑖 )
𝐿𝑒𝑡 𝑥 2 log 5 = 𝑧
𝑑𝑧
⇒ 2𝑥𝑑𝑥 =
log 5
𝑑𝑧 1 𝑑𝑧
⇒ 𝑑𝑥 = 𝑧
= . 𝑥 0 ∞
2√ .log 5 2√log 5 √𝑧
log 5
𝑧 0 ∞
∴ From (𝑖 ), we get
∞ ∞
−𝑥 2
1 𝑑𝑧
∫5 𝑑𝑥 = ∫ 𝑒 −𝑧 .
2√log 5 √𝑧
0 0
∞ 1
1 −
=
2√log 5
∫0 𝑒 −𝑧 𝑧 2 𝑑𝑧
1
1 √𝜋
= Γ( ) =
2√log 5 2 2√log 5
𝟏 𝟑 𝟑
𝟑𝝅
12. (i) P.T ∫𝟎 𝒙𝟐 (𝟏 − 𝒙)𝟐 𝒅𝒙 = 𝟏𝟐𝟖 [CH-2007]
Solution :-
We have
1
3 3 5 5
∫ 𝑥 2 (1 − 𝑥 )2 𝑑𝑥 = 𝛽 ( , )
2 2
0
5 5
Γ (2) Γ (2)
=
5 5
Γ (2 + 2)
2
3 1
{ . √𝜋}
= 2 2 [∵ Γ (5) = 4!]
4!
9 1 3𝜋
= 𝜋× = (𝑝𝑟𝑜𝑣𝑒𝑑)
16 4.3.2.1 128
𝟏 𝟓
𝟐
12. (ii) P.T ∫𝟎 𝒙𝟑 (𝟏 − 𝒙𝟐 )𝟐 𝒅𝒙 = 𝟔𝟑. [CH-2004]
Solution :-
and
Let 𝑥 2 = 𝑧, then 2𝑥𝑑𝑥 = 𝑑𝑧
𝑑𝑧 𝑥 0 1
⇒ 𝑑𝑥 =
2√𝑧 𝑧 0 1
1 1
5 3 5 𝑑𝑧
∴ ∫ 𝑥 3 (1 − 𝑥 2 )2 𝑑𝑥 = ∫ 𝑧 2 (1 − 𝑧)2 .
2√𝑧
0 0
1
1
= ∫ 𝑧 (1 − 𝑧)5/2 𝑑𝑧
2
0
1 7
= 𝛽 (2, )
2 2
~8~
7
1 Γ(2)Γ (2) Γ(m)Γ(n)
= [∵ 𝛽 (𝑚, 𝑛) = ]
2 Γ (11) Γ(m + n)
2
7
1 Γ (2) nΓ(n), n > 0
= [∵ Γ(n + 1) = { ]
2 9 . 7 . Γ (7) n! , if n ∈ ℕ
2 2 2
1 4 2
= × =
2 63 63
𝟏 𝟐
𝟏 {𝚪 ( )}
𝟒
14. (i) P.T ∫𝟎 √𝟏 − 𝒙𝟒 𝒅𝒙 = .
𝟔√𝟐𝝅
Solution :-
Let 𝑥 4 = 𝑧 ⇒ 4𝑥 3 𝑑𝑥 = 𝑑𝑧 and
𝑑𝑧
⇒ 𝑑𝑥 = 3
𝑥 0 1
4 𝑧4 𝑧 0 1
1 1
𝑑𝑧
∴ ∫ √1 − 𝑥 4 𝑑𝑥 = ∫ √1 − 𝑧 . 3
0 0 4 𝑧4
1
1 3 1
= ∫ 𝑧 −4 (1 − 𝑧)2 𝑑𝑧
4
0
1 1 3
= 𝛽( , )
4 4 2
1 3
1 Γ (4) Γ (2) Γ(m)Γ(n)
= [∵ 𝛽(𝑚, 𝑛) = , 𝑤ℎ𝑒𝑟𝑒 𝑚 > 0, 𝑛 > 0]
4 7 Γ(m + n)
Γ (4)
1 1
1 Γ (4) . 2 √π
=
4 3 Γ (3)
4 4
1 1
1 Γ (4) Γ (4) √π
=
6 Γ (3) Γ (1)
4 4
2
1 1 2 1 2
1 {Γ (4)} √𝜋 1 {Γ (4)} {Γ (4)}
= = = [∵ Γ(𝑚)Γ(1 − 𝑚) = 𝜋𝑐𝑜𝑠𝑒𝑐 𝑚𝜋, 0 < 𝑚 < 1]
6 𝜋 𝑐𝑜𝑠𝑒𝑐 𝜋 6√𝜋 √2 6√2𝜋
4
𝟏
𝟏 𝒅𝒙 √𝝅 𝚪( )
𝟒
14. (ii) P.T . ∫𝟎 = . 𝟑 .
√𝟏−𝒙𝟒 𝟒 𝚪( )
𝟒
Solution :-
Let 𝑥 4 = 𝑧 ⇒ 4𝑥 3 𝑑𝑥 = 𝑑𝑧
𝑑𝑧
⇒ 𝑑𝑥 = 3 and
4𝑧 4
1 1
𝑥 0 1
𝑑𝑥 𝑑𝑧
∴ ∫ = ∫ 3/4 𝑧 0 1
√1 − 𝑥 4 4𝑧 (1 − 𝑧)1/2
0 0
1
1 3 1
= ∫ 𝑧 −4 (1 − 𝑧)−2 𝑑𝑧
4
0
~9~
1 1 1
= 𝛽( , )
4 4 2
1 1
1 Γ (4) Γ (2)
=
4 3
Γ (4)
1
√π Γ (4) 1
= [∵ Γ ( ) = √𝜋]
4 Γ( )3 2
4
𝝅
𝟏 1 3 π
14. (iii) P.T ∫𝟎𝟐 √𝒕𝒂𝒏 𝒙 𝒅𝒙 = 𝟐 Γ (4) Γ (4) = 2.
√
Solution :-
We have
𝜋/2 𝜋/2
√𝑠𝑖𝑛 𝑥
∫ √𝑡𝑎𝑛 𝑥 𝑑𝑥 = ∫ 𝑑𝑥
√𝑐𝑜𝑠 𝑥
0 0
𝜋/2
𝝅/𝟐 𝒅𝒙 𝝅/𝟐
14. (iv) P.T ∫𝟎 × ∫𝟎 √𝒔𝒊𝒏 𝒙 𝒅𝒙 = 𝝅
√𝒔𝒊𝒏 𝒙
Solution :-
We have
𝜋/2 𝜋/2
The given integral = ∫0 𝑠𝑖𝑛−1/2 𝑥 cos 0 𝑥 𝑑𝑥 × ∫0 𝑠𝑖𝑛𝜋/2 𝑥 cos 0 𝑥𝑑𝑥
𝜋
1 1 2
1 −2+1 0 +1 1 + 1 0 + 1 1 𝑝+1 𝑞+1
) . 𝛽 (2
𝑝 𝑞
= 𝛽( , , ) ∵ ∫ 𝑠𝑖𝑛 𝜃𝑐𝑜𝑠 𝜃 𝑑𝜃 = 2 𝛽 ( 2 , 2 )
2 2 2 2 2 2 0
[ 𝑝 > −1, 𝑞 > −1 ]
1 1 1 1 3 1
= 𝛽( , ) . 𝛽( , )
2 4 2 2 4 2
1 1 3 1
1 Γ (4) Γ (2) Γ (4) Γ (2) Γ(m)Γ(n)
= . [∵ 𝛽(𝑚, 𝑛) = , 𝑤ℎ𝑒𝑟𝑒 𝑚 > 0, 𝑛 > 0]
4 Γ (1 + 1) Γ (3 + 1) Γ(m + n)
4 2 4 2
~ 10 ~
1 1 3 1
1 Γ (4) Γ (2) Γ (4) Γ (2)
= .
4 3 5
Γ (4) Γ (4)
1 2
1 Γ (4) (√π) 2
= . = (√𝜋) = 𝜋 [𝑝𝑟𝑜𝑣𝑒𝑑 ]
4 1 1
4 Γ (4)
𝒎+𝟏
𝝅/𝟐 𝝅/𝟐 √𝝅 𝚪( 𝟐 )
10. Show that (i) ∫𝟎 𝒄𝒐𝒔𝒎 𝒙 𝒅𝒙 = ∫𝟎 𝒔𝒊𝒏𝒎 𝒙 𝒅𝒙 = . , 𝒎 > −1.
𝟐 𝚪(𝒎+𝟐)
𝟐
𝝅/𝟐 𝟏𝟐𝟖 𝝅/𝟐 𝟑𝝅 𝝅/𝟐 𝟖
(ii) ∫𝟎 𝒔𝒊𝒏𝟗 𝒙 𝒅𝒙 = 𝟑𝟏𝟓. (iii) ∫𝟎 𝒄𝒐𝒔𝒂 𝒙 𝒅𝒙 = . (iv) ∫𝟎 𝒔𝒊𝒏𝟒 𝒙 𝒄𝒐𝒔𝟓 𝒙 𝒅𝒙 = 𝟑𝟏𝟓.
𝟏𝟔
𝝅/𝟐 𝟑𝝅 𝝅/𝟐 𝟐
(v) ∫𝟎 𝒔𝒊𝒏𝟒 𝒙 𝒄𝒐𝒔𝟒 𝒙 𝒅𝒙 = 𝟐𝟓𝟔. (vi) ∫𝟎 𝒔𝒊𝒏𝟒 𝒙 𝒄𝒐𝒔𝟑 𝒙 𝒅𝒙 = 𝟑𝟓
(vi)Solution:-We have
𝜋
𝜋/2 2
1 4+1 3+1 𝑝 𝑞
1 𝑝+1 𝑞+1
∫ 𝑠𝑖𝑛4 𝑥 𝑐𝑜𝑠 3 𝑥 𝑑𝑥 = 𝛽 ( , ) ∵ ∫ 𝑠𝑖𝑛 𝜃𝑐𝑜𝑠 𝜃 𝑑𝜃 = 2 𝛽 ( 2 , 2 )
2 2 2 0
0
[ 𝑝 > −1, 𝑞 > −1 ]
1 5
= 𝛽 ( , 2)
2 2
5
1 Γ (2) Γ(2) Γ(m)Γ(n)
= [∵ 𝛽 (𝑚, 𝑛) = , 𝑤ℎ𝑒𝑟𝑒 𝑚 > 0, 𝑛 > 0]
2 Γ (9) Γ(m + n)
2
5
1 Γ (2)
= .
2 7 . 5 Γ (5)
2 2 2
2
= [𝑝𝑟𝑜𝑣𝑒𝑑 ]
35
𝟐 𝟏
𝟏𝟔𝝅
17. P.T ∫𝟎 𝒙(𝟖 − 𝒙𝟑 )𝟑 𝒅𝒙 = 𝟗√𝟑
Solution :- And
Let 𝑥 3 = 8𝑧, then 3𝑥 2 𝑑𝑥 = 8𝑑𝑧
8 𝑑𝑧 𝑥 0 2
⇒ 𝑑𝑥 = . .
3 ( )23 𝑧 0 1
8𝑧
1
2 1 3
1 18 1
∴ ∫ 𝑥 (8 − 𝑥 3 )3 𝑑𝑥 = ∫(8𝑧) (8 − 8𝑧)3 . 𝑑𝑧
3 ( )23
0 0 8𝑧
1
8 1 1
= ∫ 𝑧 −3 (1 − 𝑧)3 𝑑𝑧.
3
0
8 2 4
= 𝛽( , )
3 3 3
2 4
8 Γ (3) Γ (3)
=
3 Γ(2)
2 1
8 Γ (3) 1/3 Γ(3) 𝑛Γ(n), if n > 0
= [∵ Γ(m + 1) = { ]
3 1 𝑛! , 𝑖𝑓 𝑛 ∈ ℕ
~ 11 ~
8 2 1
= Γ( )Γ( )
3 3 3
8𝜋 𝜋
= 𝑐𝑜𝑠𝑒𝑐 [∵ Γ(m)Γ(1 − m) = 𝜋𝑐𝑜𝑠𝑒𝑐 𝑚𝜋, 0 < 𝑚 < 1]
9 3
8𝜋 2 16𝜋
= × = [𝑝𝑟𝑜𝑣𝑒𝑑 ]
9 √3 9√3
𝒃
(13.) Prove that ∫𝒂 (𝒙 − 𝒂)𝒎−𝟏 (𝒃 − 𝒙)𝒏−𝟏 𝒅𝒙 = (𝒃 − 𝒂)𝒎+𝒏−𝟏 𝜷(𝒎, 𝒏), 𝒎 > 0, 𝑛 > 0
𝒃 𝟑 (𝒃−𝒂)𝟔
Hence prove that ∫𝒂 (𝒙 − 𝒂) (𝒃 − 𝒙)𝟐 𝒅𝒙 = . [CH-2002,2006]
𝟔𝟎
Solution :- And
𝑥−𝑎
Let 𝑧 = 𝑏−𝑎 , then 𝑥 − 𝑎 = 𝑧(𝑏 − 𝑎)
𝑥 𝑎 𝑏
⇒ 𝑥 = 𝑎 + 𝑧 (𝑏 − 𝑎 )
𝑧 0 1
∴ 𝑑𝑥 = (𝑏 − 𝑎)𝑑𝑧
𝑏 1
∴ ∫(𝑥 − 𝑎 )𝑚−1 ( 𝑏−𝑥 )𝑛−1 𝑑𝑥 = ∫{𝑧 (𝑏 − 𝑎)}𝑚−1 . {(𝑏 − 𝑎) − 𝑧(𝑏 − 𝑎)}𝑛−1 (𝑏 − 𝑎)𝑑𝑧
𝑎 0
1
~ 12 ~